Salzburgers and Their Descendants - Kleckley, Russell C. (Georgia Open History Library, 1953)
Salzburgers and Their Descendants is the original account of the lives and history of a colony of German Protestants who emigrated to Georgia in 1734. Following their arrival, they settled twenty-five miles north of Savannah, in Ebenezer, to create new lives for themselves in a "New World" of religious freedom. The account of this colony is beneficial to the study of Georgia history, as it furthers an understanding of the reasons for emigrating and of the struggles that settlers faced on arrival. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.